Neuroprotective Effects of Inhaled Xenon for Sedation Compared With Propofol Intravenous Sedation in Severe Ischemic Stroke - O. A. Grebenchikov; A. K. Evseev; V. V. Kulabuchov; A. N. Kuzovlev; S. S. Petrikov; G. R. Ramazanov; Sh. Gh. Khusainov; R. A. Cherpakov; A. K. Shabanov; A. I. Spichko (Неотложная медицинская помощь)
ABSTRACTS  Ischemic stroke occupies a leading position among the causes of mortality and disability. Long-lasting motor and cognitive impairments, a decrease in the level of consciousness over time aggravate the course of the disease, leading to immobilization syndrome and comorbidity load, which contributes to the development of life-threatening conditions in this category of patients. In this regard, the search for new neuroprotective strategies used at an early stage and capable of minimizing the severe consequences of stroke for the patient in particular and society as a whole seems extremely relevant. The paper presents the effect of inhaled xenon for sedation in patients with severe ischemic stroke on the level of consciousness and severity of neurological disorders, and also shows its effect on S100B protein, a marker for blood brain barrier damage.AIM OF STUDY To evaluate the effect of inhaled xenon for sedation in comparison with propofol intravenous sedation on the dynamics of the level of consciousness, the severity of neurological dysfunction and changes in the concentration of astroglial-derived S100B protein in severe ischemic stroke.MATERIAL AND METHODS The research was conducted on two groups of patients comparable in age, gender, comorbid background, as well as the severity of the underlying disease. In both groups, the condition of patients required the start of mechanical ventilation immediately after admission to the intensive care unit. Group I (control, n=12). After intubation and the start of ventilation, patients were sedated with propofol at a dose of 1-2 mg/ kg / hour for 24–72 hours. Group II (xenon, n=12). After intubation and the start of ventilation, patients underwent xenon inhalation at a concentration of 40 vol. % for the first 6 hours. If it was necessary to continue sedation after the end of xenon inhalation, propofol was used in doses similar to Group I. Neurological status was assessed on days 1, 3 and 8 using the Glasgow Coma Scale (GCS), the Full Outline of UnResponsivness (FOUR) score and the National Institutes of Health Stroke Scale (NIHSS). The critical analysis of the value of S100B as a marker of brain damage was carried out before the start of sedation, on the 3rd and 8th days.RESULTS Xenon inhalation (40 vol. %) in comparison with propofol intravenous sedation significantly increases the level of consciousness in patients with severe ischemic stroke (p=0,026), reduces neurological disorders assessed using NIHSS (p=0,007) on day 7, and also reduces serum S100B levels on day 3 (p<0,05) after ischemic stroke.CONCLUSION Our open randomized clinical trial of xenon inhalation versus propofol intravenous sedation revealed the neuroprotective properties of xenon anesthesia in patients with severe ischemic stroke. Based on the obtained clinical and laboratory data, it can be concluded about the effective implementation of the neuroprotective effects of xenon in the administration scheme used in the research.